PENGARUH TIME PRESSURE, TINDAKAN SUPERVISI, AUDIT RISK, MATERIALITAS, PROSEDUR REVIEW, DAN KESADARAN ETIS TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT DI BPK-RI PERWAKILAN BALI - I Made Wianto Putra; A.A. Raka Emas Wicahyani (Faculty of Economics and Business, Universitas Warmadewa, 2018)
Abstract The purpose of this study was to examine the effects of time pressure, audit risk, materiality, review procedures, and ethical awareness of premature termination of audit procedures. The research was conducted at BPK-RI Bali Representative. The number of samples used were 50 respondents. Data analysis techniques used in this study are instrument test, classical assumption test, and multiple linear regression analysis. Time pressure test results have a positive effect on premature termination of audit procedures. Supervision actions have a negative effect on premature termination of audit procedures. Audit risk positively affects the premature termination of audit procedures. Materiality positively affects premature discontinuation of audit procedures. Review procedures negatively impact the premature termination of audit procedures. Ethical awareness negatively affects the premature discontinuation of audit procedures. Keywords: time pressure, supervision actions, audit risk, materiality, review procedures, ethical awareness, premature discontinuation of audit procedures